A Concept Analysis of Patient-centered Communication - Cheon, Hongjin; Han, A Young (Chonnam Research Institute of Nursing Science, 2022)
Purpose: The nature of patient-centered communication matters in medical practice. Active mutual communication between caregivers and patients helps the latter to understand the disease and take part in the process of making appropriate decisions based on the provided information. The purpose of this paper is to analyze the literature on patient-centered communication and to generate operational definitions. Methods: Data were collected through a literature review using PubMed and CINAHL. The concept of patient-centered communication was analyzed using the Walker and Avant eight-step method for concept analysis. Results: Three defining attributes of patient-centered communication were identified: Respecting the patient's point of view, Making shared goals, and Patient-involved decision-making. Conclusion: The attributes identified in this study could be applied to studies that seek to verify the effectiveness of decision-making intervention programs in improving patient outcomes. KCI Citation Count: 0